Pain Input Impairs Recovery after Spinal Cord Injury: Treatment with Lidocaine - Turtle, Joel D. (J Neurotrauma, 2017)
More than 90% of spinal cord injuries are caused by traumatic accidents and are often associated with other tissue damage (polytrauma) that can provide a source of continued pain input during recovery. In a clinically relevant spinal cord contusion injury model, prior work has shown that noxious stimulation at an intensity that engages pain (C) fibers soon after injury augments secondary injury and impairs functional recovery. Noxious input increases the expression of pro-inflammatory cytokines (interleukin 1β and 18), cellular signals associated with cell death (caspase 3 and 8), and physiological signs of hemorrhage. Here, it is shown that reducing neural excitability after spinal cord injury (SCI) with the local anesthetic lidocaine (micro-injected by means of a lumbar puncture) blocks these adverse cellular effects. In contrast, treatment with an analgesic dose of morphine had no effect. Contused rats that received nociceptive stimulation soon after injury exhibited poor locomotor recovery, less weight gain, and greater tissue loss at the site of injury. Prophylactic application of lidocaine blocked the adverse effect of nociceptive stimulation on behavioral recovery and reduced tissue loss from secondary injury. The results suggest that quieting neural excitability using lidocaine can reduce the adverse effect of pain input (from polytrauma or surgery) after SCI.